Biochemical capacitance of geobacter sulfurreducens biofilms - Bueno, Paulo R. (2015)
An electrical model able to decouple the electron pathway from microbial cell machinery impedance terms is introduced. In this context, capacitance characteristics of the biofilm are clearly resolved. In other words, the model allows separating, according to the advantage of frequency and spectroscopic response approach, the different terms controlling the performance of the microbial biofilm respiratory process and thus the directly related electricity production process. The model can be accurately fitted to voltammetry measurements obtained under steady-state conditions and also to biofilm discharge amperometric measurements. The implications of biological aspects of the electrochemical or redox capacitance are discussed theoretically in the context of current knowledge with regard to structure and physiological activity of microbial Geobacter biofilms.